The cytogenetics of polar bodies: insights into female meiosis and the diagnosis of aneuploidy. - Fragouli, E; Alfarawati, S; Goodall, N; Sánchez-García, J; Colls, P; Wells, D (2011)
Female meiosis is comprised by two cell divisions, meiosis I (MI) and II (MII) and two different stages at which the development of the oocyte is temporarily halted. In the case of MI, this pause can potentially last for four to five decades. This added layer of complexity distinguishes female gametogenesis from its male counterpart. The single most important genetic factor impacting human reproductive success is aneuploidy. Aneuploid embryos may undergo permanent arrest during preimplantation development, fail to implant or spontaneously abort. Most aneuploidies originate during female meiosis and become increasingly common with advancing maternal age. To shed further light on the nature of aneuploidy in human oocytes, we utilized comparative genomic hybridization (CGH) to provide a detailed cytogenetic analysis of 308 first and second polar bodies (PBs). These were biopsied from fertilized oocytes, generated by 70 reproductively older women (average maternal age of 40.8 years). The total oocyte abnormality rate was 70%, and MII anomalies predominated over MI (50% aneuploidy rate versus 40.3%). Both whole chromosome non-disjunction and unbalanced chromatid predivision were seen, but the latter was the dominant MI aneuploidy-causing mechanism. Chromosome losses occurred more frequently than chromosome gains, especially during MI. Chromosomes of all sizes were found to participate in aneuploidy events, although errors involving smaller chromosomes were more common. These data reveal the spectrum of aneuploidies arising after each meiotic division, indicating that oocyte-derived abnormalities present at conception differ from those observed in established pregnancies. It is also clear that advancing maternal age had a significant adverse effect on female meiosis, and that this effect is most pronounced in MII. Indeed, our data suggest that MII may be more susceptible to age-related errors than MI.